How forage characteristics influence behaviour and intake in small ruminants: A review - Baumont R.; Prache S.; Meuret M.; Morand-Fehr P. (Sheep and goat nutrition: Intake, digestion, quality of products and rangelands, 2000)
Small ruminant production systems vary widely, from high producing dairy goats to suckling ewes on rangelands. However, in all environments feed characteristics influence animals' motivation to eat, dietary choices and ultimately nutrient intake. This review highlights the common feed factors that influence feeding behaviour and intake, although their expression and consequences depend on the environment. The main characteristics of feeding behaviour are described in terms of the satiation process and motivation to eat. The main feed factors that influence intake are then reviewed. The relationship between the nutritive value of forages and their voluntary intake is well established. The relationship between nutritive value and palatability of feeds is discussed in the light of recent work on how feed characteristics are learned.
8. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1998/09/03-05, Grignon (France)